Pharmacist-Pharmacy Technician Intraprofessional Collaboration and Workplace Integration: Implications for Educators - Maryam Jetha; Ali Walji; Paul Gregory; Dalya Abdulla; Zubin Austin (MDPI AG, 2020)
Globally, concerns have been expressed regarding the impact of regulation of pharmacy technicians. After more than a decade of experience with technician regulation in Ontario, Canada, uptake of the full scope of practice for technicians has been sporadic at best. The objective of this study was to examine barriers and facilitators to intraprofessional collaboration between pharmacists and pharmacy technicians for the purpose of identifying possible curricular or educational interventions to enhance workplace integration. A qualitative, interview-based study of 24 pharmacists, technicians, educators, pharmacy managers, and owners was undertaken using a semi-structured interview guide. Key findings of this research include: (i) Confirmation of suboptimal utilization of regulated technicians in practice; (ii) identification of crucial knowledge and skills gaps for both pharmacists and technicians; and (iii) proposals for undergraduate education and training, and continuing professional development learning opportunities to address these gaps. In order to achieve the promise and potential of regulation of pharmacy technicians, system-wide change management-beginning with education-will be required and will benefit from multiple stakeholder engagement and involvement.